2017
DOI: 10.3390/buildings7020028
|View full text |Cite
|
Sign up to set email alerts
|

Annual Performance of Sensible and Total Heat Recovery in Ventilation Systems: Humidity Control Constraints for European Climates

Abstract: Ensuring a comfortable indoor air quality requires a minimum fresh air supply by ventilation. Moreover, the improvement of the air tightness in new and refurbished high performance buildings enhances the role of mechanical ventilation and its importance in further increasing the energy efficiency. Indeed, a reduction of the ventilation load can be achieved by installing air-to-air heat recovery devices, whose potential energy savings can be easily assessed by means of their nominal effectiveness. However, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
2
4
0
1
Order By: Relevance
“…The main results obtained in the inlet and outlet nozzle zones during the sampling process in the open loop wind tunnel are reflected in Table 1 and in the CFD simulations of the third test shown in Figure 7. The inlet conditions-consistent with previous research works about this validation procedure [27][28][29]-were the same in the real process than in the simulation, as we can see, for instance, in the third test of Table 1 and in Figure 7, in terms of relative humidity (Figure 7a) and velocity (Figure 7b…”
Section: Experimental Nozzle Results and Simulation Validationsupporting
confidence: 88%
See 1 more Smart Citation
“…The main results obtained in the inlet and outlet nozzle zones during the sampling process in the open loop wind tunnel are reflected in Table 1 and in the CFD simulations of the third test shown in Figure 7. The inlet conditions-consistent with previous research works about this validation procedure [27][28][29]-were the same in the real process than in the simulation, as we can see, for instance, in the third test of Table 1 and in Figure 7, in terms of relative humidity (Figure 7a) and velocity (Figure 7b…”
Section: Experimental Nozzle Results and Simulation Validationsupporting
confidence: 88%
“…Figure 8 shows the maximum velocity value in the nozzle-diffuser throat for an inlet velocity of 5 m/s and relative humidity of 95%. The maximum relative humidity of 100% and its related moist The inlet conditions-consistent with previous research works about this validation procedure [27][28][29]-were the same in the real process than in the simulation, as we can see, for instance, in the third test of Table 1 and in Figure 7, in terms of relative humidity (Figure 7a) and velocity (Figure 7b) distributions, and even in point values in the centre line.…”
Section: Nozzle Diffuser Simulation Under Internal Flowsupporting
confidence: 88%
“…Дослідження показують низьку ефективність їх застосування як в цілях температурної, так і вологої обробки повітря [29].…”
Section: результати дослідженняunclassified
“…There are also the uncertainties of future energy prices, which may prolong or shorten this period. In a recent research [21] it was concluded that the payback period of a sensible recovery HE, in 24-hour operating ventilation systems, is less than 4 months in Mediterranean countries. Any increase in electricity price by 10% reduces the cost savings rate by 5% in the case of full occupancy and by about 8% in the case of half occupancy.…”
Section: Energy Analysismentioning
confidence: 99%